Changes in Photosynthetic Pigment of Wheat(Triticum Aestivum L. Var. Bari Gom-25) As Affected By Naa and N-Fertilizer (Dhaka University Journal of Biological Sciences, 2022)
A field experiment was conducted to investigate the changes inphotosynthetic pigment of BARI Gom-25 as affected by foliar spray of NAA andN-fertilizers. The experiment consisted of seven different concentrations of NAA(NAA0 = 0, NAA1 = 10, NAA2 = 20, NAA3 = 30, NAA4 = 40, NAA5 = 50 and NAA6 =60 ppm) and five N-levels (F0=0, F1=25, F2=50, F3=75 and F4=100% of therecommended dose) and their 35 combination treatments. Results revealed thatfoliar application of 40 ppm NAA (NAA4) produced higher chlorophyll a contentat all stages (tillering, flowering and grain filling) and were significantly higherthan control at tilling and flowering stages. Chlorophyll b and carotenoidcontents did not show any general trend to NAA at any stage except at tillingstage. Application of 50% of the recommended N-fertilizer (F2) producedsignificantly maximum photosynthetic pigment contents at tilling stage whereas,at flowering stage the same results were obtained from 100% of therecommended N-fertilizers (F4) but with few exceptions. At grain filling stage,photosynthetic pigment did not show any general trend to N-fertilizerapplication. Findings on combined effects indicated that 20 and 30 ppm NAA incombination with 50% N-fertilizer (NAA2F2 and NAA3F2) had producedsignificantly maximum chlorophyll a content at tilling stage. However, atflowering stage the highest chlorophyll a content was noted from NAA2F4treatment (20 ppm NAA in combination with 100% N-fertilizer). Findings alsorevealed that combined application of NAA and N-fertilizer had not resulted anygeneral trend on chlorophyll b and carotenoid contents in most of the caseswhere the maximum value in photosynthetic pigment was found depending onthe concentrations of NAA, fertilizer dose and plant growth stages.Dhaka Univ. J. Biol. Sci. 31(1): 169-176, 2022 (January)